Effect of organic fertilizer and chemical fertilizer on growth and yield of Wheat (Triticum aestivm) - Sarkawt Zorab Mohammed; Fatih Karim Hama Ali; Arsalan Azeez Marif (Faculty of Agriculture, Merdeka University Surabaya, Indonesia, 2023)
Current study was conducted in pot and open field of Bakrajo Technical Institute BTI Field, Sulaimani Polytechnic University, Sulaimani Iraq, during growing season of 2021-2022. The pot experiment was under a one-year rotation of (Triticum aestivum) winter wheat open field cultivation. The applications were PL (poultry litter 50 gm/pot), LM (livestock manure50 gm /pot), and CF (chemical fertilizer 20:20:20 N:P: K in 3 gm/pot) ,the applications testes on growth and yield parameters(Biology.yield/plant(g), 1000-grain weight(g), Weight of spikes/plant(g) Spike length (cm), No. of grains/ spike, No. of spikes/plant Weight, Weight of grains/spike(g), Grain yield/Plant(g)and Harvest Index and the mention application compared withcontrol without using of any chemical ad organic fertilizers .(in A completely randomized design (CRD) with three replications with interaction. The results indicated that applications of interaction of poultry with chemical fertilizer20:20:20 N:P: K in 3 gm/pot positive effect and poultry (poultry litter 50 gm/pot), chemical fertilizer fertilizer20:20:20, interaction of Animal manure with chemical fertilizer and Animal manure (5.313,4.838, 5.833, 3.853, 3.225,1.217), respectively influenced. however, replications effect indicated that R1 top influence and R3, R2 (respectively influenced.